Intramedullary use of an antibiotic synthetic bone filler in diabetics undergoing metatarsal amputation(s) - Thomas Poynter, DPM; Kaitlyn J. Loesel, DPM; Michael Sweeney, DPM; Alden Simmons, DPM; Brandon Kitchens, DPM; Timothy Ford, DPM; Nicholas Laco, DPM (Foot & Ankle Surgery: Techniques, Reports & Cases)
The use of intramedullary devices to treat osteomyelitis has been documented as being effective and safe. Technology has limited the use of this technique to long bones with application on an intramedullary nail or rod. In this paper, we describe a novel technique using antibiotic synthetic bone void filler (ASBVF) applied into the medullary canal of a transmetatarsal amputation. This backfills a necrotic void and creates a bioabsorbable, antibiotic impregnated filler to resist and treat further advancement or recurrence of osteomyelitis after resection.